Role of N6-methyladenosine methyltransferase component RBM15 in cancer progression and its therapeutic potential - Wenxiang Shen; Yulong Ma; Chunwang Yang; Shishun Yan; Kaishan Ye (Discover Oncology)
Abstract Cancer ranks as a primary cause of mortality globally, and the study of its molecular markers and regulatory mechanisms holds paramount importance. N6-methyladenosine (m⁶A) represents the predominant modification in messenger RNA (mRNA), influencing key biological processes including RNA stability, splicing, and translation. The dynamic modulation of m⁶A modification is mediated by an array of enzymes comprising methyltransferases (“writers”), demethylases (“erasers”), and m⁶A-binding proteins (“readers”).As a pivotal member of the m⁶A “writer” family, RNA binding motif protein 15 (RBM15) facilitates the recruitment of the methyltransferase complex (MTC) to mRNA, thus orchestrating the addition of m⁶A modifications. Although prior research has underscored the critical role of m⁶A in oncogenesis, the precise mechanisms through which RBM15 operates in cancer are yet to be elucidated. This study endeavors to elucidate the structural characteristics and functional roles of RBM15, investigate its potential regulatory mechanisms across diverse tumors, uncover its distinct functions in tumor genesis, progression, and metastasis, and evaluate the therapeutic potential of targeting RBM15 in cancer treatment.